(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Bhringaraja (Eclipta prostrata (L.)) is a plant widely used as a remedy for liver disorders, Anaemia etc. The drug is said to have three varieties based on the colour of its flower. Peetha Bhringaraja is the yellow flowered variety of Bhringaraja. The drug is botanically identified as Wedelia chinensis (Osbeck) Merrill belongs to the family Asteraceae. The drug is not that much abundantly seen nowadays. Wedelia trilobata is another similar invasive species belongs to the same family Asteraceae. The IUCN has listed Wedelia Trilobata in its 100 world’s worst invasive alien species. Florida exotic plant pest council considered it as category 2 invader. Due to its invasion most of the similar Wedelia species got replaced. Pharmacognosy is the only reliable tool to differentiate among plants. For the purpose of utilisation of genuine source of Wedelia chinensis (Osbeck) Merrill, the plant was identified and detailed macroscopy and microscopy of root, stem and leaf along with the powder microscopy of whole plant is done.